2022
DOI: 10.21203/rs.3.rs-1568313/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inconsistent Condom Use among Street-Based Transgender Sex Workers in Lahore, Pakistan: Socio-Ecological Analysis based on a Qualitative Study

Abstract: Background: A large amount of new HIV infections worldwide is observed amongst key populations which include e.g. commercial sex workers or transgender people and their respective sexual partners. Therefore, this study examined the multi-level context of inconsistent condom use (ICU) in sexual interactions of transgender street-based workers (KSWs) with commercial and non-commercial sexual partners in Lahore. Methods: We conducted 20 in-depth interviews with street-based KSWs to investigate challenges to consi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A study published in the NCBI found that transgender people in Pakistan face social marginalisation in addition to physical and verbal assault, which drives many of them into commercial sex work. Economic marginalisation, restricted access to education and healthcare, and social stigma all contribute to transgender people's experiences of social exclusion (Bano et al ., 2023). Because of this discrimination, they are less likely to find gainful employment and are more likely to be victims of workplace abuse and exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…A study published in the NCBI found that transgender people in Pakistan face social marginalisation in addition to physical and verbal assault, which drives many of them into commercial sex work. Economic marginalisation, restricted access to education and healthcare, and social stigma all contribute to transgender people's experiences of social exclusion (Bano et al ., 2023). Because of this discrimination, they are less likely to find gainful employment and are more likely to be victims of workplace abuse and exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…It is related to Kigongi Ward in Kabale Town and is associated with unsafe abortion and the spread of gonorrhea, syphilis, and HIV/AIDS (Bossard et al, 2022). According to Bano et al (2023) the majority of assessments of prostitution, both men and women engage in prostitution for monetary gain, either continuously as relative beginners or for a moment as professionals. Prostitution is a common choice for young women who seek to subvert restrictive gender stereotypes that limit women's sexuality to romantic relationships and prevent marriages (Onanuga, 2023).…”
Section: Introductionmentioning
confidence: 99%